2019
DOI: 10.1097/md.0000000000014636
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adjunctive corticosteroids therapy for patients with severe community-acquired pneumonia

Abstract: Background: The systemic use of corticosteroids for patients in severe community-acquired pneumonia (CAP) remains disputed in clinical practice. We undertook a systematic review and meta-analysis to assess the efficacy and safety of corticosteroids in patients with severe CAP. Methods: We searched MEDLINE (1946 to June 2018), EMBASE (1966 to June 2018), and the Cochrane Library database for randomized controlled trials (RCTs) conducted for severe CAP. The endpoints of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
1
31
0
5
Order By: Relevance
“…For ARDS, our review showed similar results to the 1 other published systematic review 29 that included the latest published studies. For CAP, the results on which we focus are similar to those of other recent reviews [86][87][88][89] that showed that corticosteroids may reduce mortality and length of hospital stay, and increase hyperglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…For ARDS, our review showed similar results to the 1 other published systematic review 29 that included the latest published studies. For CAP, the results on which we focus are similar to those of other recent reviews [86][87][88][89] that showed that corticosteroids may reduce mortality and length of hospital stay, and increase hyperglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…Using convalescent plasma to treat critically ill patients has been included in the latest Chinese treatment protocol (Pilot Version 6). One meta-analysis showed that glucocorticoids reduce the risk of ARDS [86] . However, different studies suggest that glucocorticoids slow viral clearance [87] .…”
Section: Immune Therapymentioning
confidence: 99%
“…Similar controversies have been shown when using CSs to treat severe LRTI patients. Current clinical data suggest a potential beneficial effect in the management of severe pneumonia characterized by a "hyper inflammatory" state [183][184][185][186][187]. The mechanisms underlying this protective role of CSs as adjunctive therapy for pneumonia and bronchiolitis include the decreased production of pro-inflammatory cytokines and the consequent decreased recruitment of neutrophils [188].…”
Section: Granulocyte-targeted Therapies For Lrtimentioning
confidence: 99%